Antimicrobial Resistance Profiles of Campylobacter spp. Isolated from Broiler Chicken Meat of Estonian, Latvian and Lithuanian Origin at Estonian Retail Level and from Patients with Severe Enteric Infections in Estonia. (6th June 2015) - Mäesaar, M.; Kramarenko, T.; Meremäe, K.; Sõgel, J.; Lillenberg, M.; Häkkinen, L.; Ivanova, M.; Kovalenko, K.; Hörman, A.; Hänninen, M.‐L.; Roasto, M.
Summary: The resistance patterns of Campylobacter spp. isolated from retail broiler chicken meat originating either from Estonia, Lithuania or Latvia collected in Estonia were determined. Additionally, in collaboration with the laboratories of several Estonian hospitals, antimicrobial susceptibility patterns were determined for Campylobacter isolates from patients with severe Campylobacter enteric infections. The isolates were identified at the species level by the PCR method. Respectively, 88.8% of the isolates were C. jejuni, and 11.2% were C. coli . In total, 126 Campylobacter isolates of broiler chicken meat and human origin were tested for minimal inhibitory concentrations (MICs) with the broth microdilution VetMIC TH method (National Veterinary Institute; Uppsala, Sweden) for a total of six antimicrobials. Resistance to one or more antimicrobials was detected in 62 (63.3%) of Campylobacter broiler chicken meat isolates and in 20 (71.4%) of human‐origin isolates. Large proportions of the broiler chicken meat isolates were resistant to ciprofloxacin (60.2%). Multidrug resistance (i.e. to three or more unrelated antimicrobials) was detected in five (5.1%) C. jejuni isolates. Among the human isolates, 20 (71.4%) were resistant to fluoroquinolones, and two (7.1%) C. jejuni isolates exhibited multidrug resistance. The chicken meat isolates of Estonian origin were the most susceptible. However, a high proportion of fluoroquinolone‐resistant C. jejuni isolates were found in Latvian and Lithuanian products. The results of this study indicate that the problems caused by the inappropriate use of antimicrobials extend beyond the country in which a food originates; therefore, both domestic and international interventions and agreements are required to implement common policies on antimicrobial usage and to minimize the emergence of Campylobacter drug resistance.